A mathematical modeling approach to measure the probability of HIV-1 transmission for different high-risk groups of Pakistan - Syed Rizwan-ul-Hasan; Fatima Farrukh; Shakil Ahmed; Syed Hani Abidi (Journal of Infection in Developing Countries)
Introduction: Since 2010, the number of new HIV-1 cases has declined by 30% globally, however, in few countries, such as Pakistan, the cases have continued to increase, where the country witnessed a 57% increase in the number of new infections between 2010 and 2020. The HIV-1 epidemic in Pakistan is concentrated in certain high-risk groups, however, it is unknown which high-risk group has a higher likelihood of transmitting HIV-1 infections to vulnerable populations. This study aimed to apply mathematical probabilistic modeling to estimate the probability of HIV-1 transmission for different high-risk groups of Pakistan.